The role of international organizations in protecting the marine environment from pollution by hazardous substances and wastes: "IAEA and IMO model" (Revue El-Wahat pour les Recherches et les Etudes, 2025)
Pollution resulting from hazardous materials causes serious damage to the environment, so international organizations of all kinds and fields seek to protect the environment and mitigate the risks of pollution, whether through the development of international legal rules for the environment, or through the issuance of decisions and recommendations, and among the organizations working in the field of environmental protection We mention, for example, the International Atomic Energy Agency and the International Maritime Organization, and we aim through this study to stand on the role of the two organizations in protecting the environment and the difficulties they face.Keywords: pollution risks, International Atomic Energy Agency, International Maritime Organization, environmental protection.